The Influence of Ruangguru Media on the Learning Motivation of SMA/MA/Equivalent Students in West Bogor Regency - Selvira, Inggit; Lestari, Hana; Arsyad, Ahmad Aulia (JURNAL SAHID DA'WATII, 2022)
Since coronavirus disease 2019 (COVID-19) come to Indonesia, so many things disturbed, fom health field, economics, social culture through education. The pandemic forces all educational activities to be transferred online or known as long-range education. Using technology in the learning process is creating new problems that many teachers do not understand how to use technology, and student have difficulty to understanding the lesson, even some students lose their motivation to learn. Some parents realize this problem then help their children by enrolling them in tutoring agencies or seeking private tutors, media ruangguru is one of alternative online tutoring media that used a lot of students in indonesia. This study aims to know media ruangguru is affecting to students learning motivation.